THE RISK INSURANCE EFFICIENCY OF BUSINESS ACTIVITY IN THE AGRICULTURAL SECTOR - O. Lobova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The necessity of business activity insurance in the agricultural sector is grounded in this article. Different types of agricultural risks are described. The principles, on which the efficiency of agricultural insurance is based, are determined. Such as: voluntary; the farmers interest; risk management; multivariate product line; promote farmers efficient; equal access to subsidies from farmers; balance; transparency and coordination of the subsidies transfer; creating a reliable and multi-level system of insurance coverage; binding institute of independent examination. The different ways to determine the effectiveness of insurance are considered.